An extremum-seeking control approach for constrained robotic motion tasks. (July 2016) - Koropouli, Vasiliki; Gusrialdi, Azwirman; Hirche, Sandra; Lee, Dongheui
Abstract: In this paper, we propose two adaptive control schemes for multiple-input systems for execution of robot end-effector movements in the presence of parametric system uncertainties. The design of these schemes is based on Model Reference Adaptive Control (MRAC) while the adaptation of the controller parameters is achieved by Extremum Seeking Control (ESC). The two control schemes, which are called Multiple-Input ESC–MRAC and Multiple-Input Adaptive-Dynamic-Inversion ESC–MRAC, are suitable for linear and nonlinear systems respectively. Lyapunov and averaging analysis shows that the proposed schemes achieve practical asymptotic reference state tracking. The proposed methods are evaluated in simulations and in a real-world robotic experiment. Abstract : Highlights: Develop an adaptive control approach for execution of robot end-effector motions. Develop an ESC–MRAC control approach for state tracking of multiple-input systems. Evaluate proposed approach in simulations and a real-world robotic task.